Minimally Manipulated Mesenchymal Stem Cells for the Treatment of Knee Osteoarthritis: A Systematic Review of Clinical Evidence. (14th August 2019) - Di Matteo, B.; Vandenbulcke, F.; Vitale, N. D.; Iacono, F.; Ashmore, K.; Marcacci, M.; Kon, E.
Abstract : Background . The use of laboratory-expanded mesenchymal stem cells (MSCs) is subject to several restrictions, resulting in "minimal manipulation" methods becoming the current most popular strategy to increase the use of MSCs in an orthopaedic practice. The aim of the present systematic review is to assess the clinical applications of "minimally" manipulated MSCs, either as bone marrow aspirate concentrate (BMAC) or as stromal vascular fraction (SVF), in the treatment of knee osteoarthritis (OA). Methods . A systematic review of three databases (PubMed, ScienceDirect, and Google Scholar) was performed using the following keywords: "Knee Osteoarthritis" with "(Bone marrow aspirate) OR (bone marrow concentrate)" or with "(adipose-derived mesenchymal stem cells) OR (adipose derived stromal cells) OR (stromal vascular fraction) OR (SVF)" as either keywords or MeSH terms. The reference lists of all retrieved articles were further reviewed for identification of potentially relevant studies. Results . Twenty-three papers were included in the final analysis (10 on BMAC and 13 on SVF). Of these, only 4 were randomized controlled trials (RCTs). Bias risk evaluation, performed using a modified Coleman score, revealed an overall poor quality of the studies. In terms of clinical application, despite the apparent safety of minimally manipulated MSCs and the short-term positive clinical outcomes associated with their use, clinicians reported different preparation and administration methods, ranging from single intra-articular injections to intraosseous applications to administration in combination with other surgical procedures. Conclusions . The available literature is undermined by both the lack of high-quality studies and the varied clinical settings and different protocols reported in the few RCTs presently published. This prevents any recommendation on the use of either product in a clinical practice. Nevertheless, the use of minimally manipulated MSCs (in the form of BMAC or SVF) has been shown to be safe and have some short-term beneficial effects.